Morphological and Interfacial Engineering with a Surfactant Additive Toward High‐Performance Blade‐Coated Quantum Dot Light‐Emitting Diodes - Wei‐Zhi Liu; Hong‐Wei Duan; Shu‐Guang Meng; Dong‐Ying Zhou; Liang‐Sheng Liao (Advanced Materials Interfaces)
Abstract The development of scalable and cost‐effective solution processes for large‐area quantum light‐emitting diodes (QLEDs) remains a pressing challenge. In this work, the blade‐coating process is explored for fabricating bottom‐emitting QLEDs using a poly(3,4‐ ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) layer modified with methanol (MeOH) and polyethylene glycol (PEG). By incorporating MeOH into the PEDOT:PSS solution, a significant reduction in surface tension is achieved, resulting in thinner and more uniform films. The addition of PEG further enhanced the film quality by suppressing PEDOT aggregation and improving phase separation, which is confirmed via atomic force microscopy (AFM). These modifications not only enhanced the conductivity of the PEDOT:PSS film due to the conformation changes, but also improved energy level alignment, leading to improved hole‐injecting properties and reduced driving voltages in QLED devices. Small‐area QLEDs with the optimized PEDOT:PSS/MeOH/PEG layer demonstrated peak current efficiencies (CE) and external quantum efficiencies (EQE) comparable to those of spin‐coated devices. The best performance is observed at a PEG concentration of 0.1 mg mL−1, yielding a CE of 33.1 cd A−1 and an EQE of 26.0%. Additionally, large‐area QLEDs (25 × 25 mm) fabricated with this approach showed uniform emission and high efficiencies, underscoring the potential of the blade‐coating method for scalable production of high‐performance QLEDs.